All Days 2003
DOI: 10.2118/82235-ms
|View full text |Cite
|
Sign up to set email alerts
|

Formation Damage vs. Solid Particles Deposition Profile during Laboratory Simulated PWRI

Abstract: The importance of produced water re-injection (PWRI) is unquestionable. It is in many cases the cheapest and most environmentally friendly solution for wastewater disposal. It is also a feasible method for EOR as a water flooding mechanism. PWRI, however, suffers from a major limitation, which is the current inability in accurately predicting the lifespan and performance of its injection wells. This is due to the multitude of parameters that affect it. Current models1–2 exist that incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Non-uniform particle distribution for very short filters was reported by Al-Abduwani [33] with the amount of deposited particles exponentially decreasing with distance from the inlet of a filter according to Chang. [34] On the contrary, if particles uniformly deposit along the length of the filter, the formation of an internal cake will cause a gradual increase of inertia (Forchheimer) coefficient, α, and a gradual decrease in filter permeability, k. However, an abrupt increase in α (Fig.…”
Section: K Ajimentioning
confidence: 99%
“…Non-uniform particle distribution for very short filters was reported by Al-Abduwani [33] with the amount of deposited particles exponentially decreasing with distance from the inlet of a filter according to Chang. [34] On the contrary, if particles uniformly deposit along the length of the filter, the formation of an internal cake will cause a gradual increase of inertia (Forchheimer) coefficient, α, and a gradual decrease in filter permeability, k. However, an abrupt increase in α (Fig.…”
Section: K Ajimentioning
confidence: 99%
“…The reduced pore space may act as filter leading to an internal filtering of migrating fines in the reservoir fluid during production. Static internal filtration experiments with Bentheim sandstone have shown that a suspension containing particles with a pore throat radius to particle radius ratio of 12.5 lead to considerable permeability reduction of 90% (Al-Abduwani et al, 2003). Modeling of filter clogging affected by a suspension indicates that a ratio of 200 between effective pore size and suspension particle diameter is sufficient to clog a filter effectively (Azarov et al, 2007).…”
Section: Influence On Well Productivitymentioning
confidence: 99%
“…[10] Abduwani et al . [11] Test is required. Several forms of this rate law have been suggested and an example is shown below [14] :…”
Section: Authorsmentioning
confidence: 99%